Impact of Training Program to the Improvement of Teaching Competency in Adaptive Physical Education - Komar Hidayat (Indonesian Journal of Disability Studies, 2019)
This study aims to determine the impact of training program to the improvement of teaching competency in Adaptive Physical Education (APE) of special educators. The provided training is competency-based and conventional training program. The teaching competency consist of professional and pedagogical of APE. This research using experiment method with factorial model 2X2. The sample are teachers of intellectual disability student. The sampling data collection using stratified cluster random sampling. The samples are 60 teachers divided to four groups that joined 60 hours of training program. The statistical analysis applied with T-Test sample paired test, Anova test (Two Way Anova with Main Effect and Interaction Effect), and PostHoc Test. The results shows that group of teachers in competency-based training program gain a high competency test score, average score higher than other groups. There is no interaction between training program and competency test result to the enhancement of teaching competency in APE.